People's Preference for Rusunawa Jogoyudan as a Residential Option - Lutfiana, Fina
The high backlog of houses in Yogyakarta City illustrates the high demand for housing. Limited land stock causes the appearance of slums and vertically directed housing, for example, the construction of Rusunawa Jogoyudan. This study aims to analyze the assessment of housing quality, perceptions, and the population's preferences. This quantitative study uses data sources obtained from literature, questionnaire, and observation, then analyzed with diagrams and cross-tabulations descriptively. This study finds that there is a compatibility between the population's perception and the housing quality assessment. Between owning and needing a house, some populations answered owning a house for housing priority and plans. The choice of housing in the future was dominated by those who plan to live in non-flat housing rather than Rusunawa Jogoyudan. There is no correlation between the preferences in housing options with the income, housing quality, housing ownership status, also perception about Rusunawa Jogoyudan. Convenience is the population's motivation not to choose Rusunawa Jogoyudan. The comfort in question is a better environment, calmer atmosphere, no rental thoughts, already own a house, easier to interact with, more flexible, wider space, no need to go up and down with stairs, and more privacy than living. at Rusunawa Jogoyudan.